CAP101 - Principles of Programming August/September 1998 - PPSKOM, Pusat Pengajian Sains Komputer (Universiti Sains Malaysia, 1998)
Stamford College Group School Of Computer Sciences (SOCS) Bachelor of Computer Science (Hons) External Degree USM Programme (In Collaboration with Universiti Sains Malaysia) August/September 1998 CAP101 - Principles of Programming Time : [3 hours] INSTRUCTIONS TO CANDIDATES: Please ensure that this examination paper contains FOUR questions in SIX printed pages before you start the examination. Answer ALL questions only. On each page, write only your Student ID.